FAKTOR YANG MEMPENGARUHI FIRM PERFORMANCE PADA PERUSAHAAN MANUFAKTUR DI BEI - Erika Agnes; Linda Santioso (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
The purpose of this research is to obtain empirical evidence about the effects of intellectual capital and audit committee on firm performance at manufacture firms listed on Indonesian Stock Exchange during the period of 2017-2019. The data used in this research was secondary data in the form of financial information from the financial statements and annual reports. There were 75 samples of manufacturing companies that have been previously selected using purposive sampling method with total of 225 data for three years. This research data was processed using EViews 10. Results shows that capital employed efficiency has a significant influence on firm performance, while human capital efficiency, structural capital efficiency, audit committee size and audit committee meeting has no significant influence on firm performance. The implication of this study is the need to increase the role of the intellectual capital and audit committee to increase firm performance which will bring a sustainable competitive advantage.